2023
DOI: 10.1111/jsr.13925
|View full text |Cite
|
Sign up to set email alerts
|

Psychobehavioural profile in narcolepsy type 1 with and without REM sleep behaviour disorder

Abstract: SummaryREM sleep behaviour disorder (RBD) is common in narcolepsy type 1 (NT1). Abnormalities in the reward system have been observed in NT1, possibly related to impaired orexin projections towards the mesolimbic reward system, but also in RBD when associated with Parkinson's disease. Our study aimed to explore the psychobehavioural profile of NT1 patients with and without RBD compared with healthy controls (HC). Forty patients with NT1 were compared with 20 sex‐ and age‐matched HC. All patients with NT1 under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
0
0
Order By: Relevance
“…This is a very interesting outcome, adding value to the study, as it is in agreement with data reported in the literature. In particular, patients with NT1 showed a greater prevalence of depression with mild and moderate symptoms compared to healthy controls [60]. According to some authors, the orexinergic system could be involved in the pathophysiology of psychiatric disorders [61].…”
Section: Discussionmentioning
confidence: 98%
“…This is a very interesting outcome, adding value to the study, as it is in agreement with data reported in the literature. In particular, patients with NT1 showed a greater prevalence of depression with mild and moderate symptoms compared to healthy controls [60]. According to some authors, the orexinergic system could be involved in the pathophysiology of psychiatric disorders [61].…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, a vPSG study, with quantitated RWA, explored the psychobehavioral profile of Narcolepsy type 1 patients with and without RBD compared with healthy controls [71]. The one significant difference found between patients with Narcolepsy type 1 with and without RBD was impaired objective attention in patients with Narcolepsy type 1-RBD.…”
Section: Rbd and Narcolepsymentioning
confidence: 99%